TESTING OF DRAWING DIES, PASSED THROUGH LOW-TEMPERATURE THERMOHYDROCHEMICAL STRENGTHENING, AT RUP “BMZ” - A. V. Demidov; A. I. Rozhkov; D. G. Sachava (Литьë и металлургия, 2007)
It is shown that inefficient for the moment theoretical study does not allow to realize fully the potential of thermo-hydrochemical strengthening of dies with the purpose of increase of their hardness.